Diurnal activity patterns of five distinct bird species in agricultural landscapes of Central Rajasthan during their non-breeding period in India - Choudhary, Rounak; Sharma, Vivek; Mathur, Praveen (Journal of Agriculture and Environmental Sciences, 2022)
The daily time activity budget explains how any species distribute their daily time for regular activities. The most typical behaviors observed in birds include foraging, feeding, roosting, flying, singing, building a nest, incubating eggs, and raising young. The temporal budgets of five bird species from three distinct feeding guilds were examined. The research area in central Rajasthan, India an ecotone of Arid and Semi-arid zones. Five bird species were examined for their behavior during the research period, with each bird being observed at least 40 (N=200) times during their non-breeding phase. The study includes the Red Collard Dove, White Eared Bulbul, Black Winged Kit, Long Tailed Shrike, and Yellow Throated Sparrow. The examination was carried out using the Scan sampling method. The data was aggregated using the un-weighted pair group method with arithmetic mean (UPGMA), and the Bray-Curtis method was used to evaluate species similarities based on time allocation in the same environment. The rates of transition between behaviors were investigated in order to understand which activity the animal does following a certain activity. Likelihood values vary from 0 to 1 were used where 0 indicated that the bird is unlikely to undertake the activity after completing any specific activity and 1 indicated that the bird has the highest probability to perform the activity after finishing any specific activity. In the behavioral research, the Yellow-throated Sparrow, Red Collard Dove, and White Eared Bulbul had the highest similarity because they devote about comparable time to similar behaviors. The results showed that the Long-Tailed Shrike and the Black-Winged Kite have very similar habits and time allocation for different tasks. When flying, the Black Winged Kite has a 0.900 chance of entering screening, and the lowest observed likelihood of flying following other behaviors such as preening is 0.100. Long-tailed Shrikes were more likely to switch from roosting to other behaviors like calling and preening, and from other activities to screening the area for food. The White-Eared Bulbul eats on insects and grains, while Red Collared Doves fly more after scanning. The Long-tailed Shrike and the Black-Winged Kite spend more time examining agricultural fields. The Red Collard Dove is among the potential pests for farmers in the study area. Long-tailed Shrike needs time to hunt, kill, and consume prey that is nearly half their body size.